Kegiatan Latihan Rutin Ekstrakurikuler PMR Menjadi Upaya Untuk Menanamkan Kepedulian Sosial Siswa - Purnamasari, Imas; Yomi Romlah, Oom; Trihastuti, Meiwatizal (STKIP Pasundan, 2025)
This research is motivated by the low social awareness among students due to globalization. Extracurricular activities such as PMR can be one of the efforts in developing social care among students. The purpose of this study was to describe the form of cultivation of students' social care through PMR extracurricular activities at SMK Pasundan 1 Cimahi. The method used in this research is a qualitative approach, the type of research used is field research. The results showed that, the form of cultivating students' social care was in the form of orientation period activities or DIKLAT, routine training every week, medical assignments and maximizing activities carried out by PMR extracurricular activities.